Back Cover: Selective Sensing of Proteins Using Aptamer Functionalized Nanopore Extended Field‐Effect Transistors (Small Methods 11/2020). Issue 11 (12th November 2020) - Ren, Ren; Wang, Xiaoyi; Cai, Shenglin; Zhang, Yanjun; Korchev, Yuri; Ivanov, Aleksandar P.; Edel, Joshua B.
Abstract : In article number 2000356, Aleksandar P. Ivanov, Joshua Edel, and co‐workers, develop a new device—aptamer functionalized nanopore extended field‐effect transistor (nexFET)—to detect proteins at the single‐molecule level with high sensitivity and selectivity. With this aptamer modified nexFET, the gate voltage facilitates single‐molecule protein detection at low concentrations (pM) with improved signal‐to‐noise, higher capture rate, and lower translocating speed.